Influence of pulsed current during high pressure sintering on crystallite size and phase composition of diamond with TiB bonding phase. (January 2018) - Jaworska, L.; Karolus, M.; Cygan, S.; Morgiel, J.; Cyboroń, J.; Laszkiewicz Łukasik, J.; Putyra, P.
Abstract: Diamond production by sintering and synthesis is known from the mid-fifties of the twentieth century. The sintering technology of PCD materials has not significantly changed even to this day. Nonetheless, there are publications providing a lot of success in the field of synthesis of diamond composite materials sintering using SPS technology, yet these studies are limited to pressures mainly up to 140 MPa. In this work HP SPS (High Pressure Spark Plasma Sintering) device, was used to sinter diamond composite with titanium‑boron bonding phase. Thus obtained material was then compared with HP-HT (High Pressure High Temperature) sintered sample, to investigate the influence of the heating by means of direct pulsed current on the crystallite size and phase composition of diamond with 10 wt% of Ti + 2B bonding phase. Both HP SPS and HP-HT processes were carried out at 8.0 ± 0.2 GPa and at the temperature of 1650 ± 50 °C during 20 s of holding time. The XRD analysis carried out showed that the different type of current used for heating has significant influence on kinetics of the sintering, which is visible in differences in phase composition and level of lattice strain, when comparing standard HP-HT with HP SPS methods. Highlights: Both HP-HT and HP SPS methods allowed to obtain materials with similar properties. For HP SPS method, smaller amount of sintering products is observed than for HP-HT. The use of pulsed current leads to lower level of lattice strain. Graphitization process is limited during HP SPS sintering.